Ferrite powder and method for producing the same
By using ferrite powder composed of spherical particles with carbon content limited to a specific range, combined with specific manufacturing steps, the magnetic characteristics and filling rate problems caused by the preparation of ambient shape particles in the ferrite powder are solved, and the excellent effects of efficient magnetic characteristics and filling rate and resin curing performance are achieved.
Patent Information
- Application Number
- CN202180010366.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-24
- Filing Date
- 2021-01-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-01-22
AI Technical Summary
Ferrite powders produced by spraying in the prior art often contain particles of ambient shape, resulting in low magnetic properties (especially saturation magnetization) and low filler filling rate.
Ferrite powders with excellent forming and filling properties are prepared by using a ferrite powder composed of normal spherical particles containing carbon-hydrogen-oxygen compounds and whose carbon content is limited to a specific range through specific manufacturing steps, including mixing, pre-granulating, pre-firing, crushing, adding lubricant and spraying.
The content of the indefinite shape particles is effectively suppressed, the saturation magnetization and filler filling rate are improved, and the curing performance of the resin is also significantly excellent when applied to the resin composition.
Smart Images

Figure BDA0003757408400000071 
Figure BDA0003757408400000101 
Figure BDA0003757408400000171
Abstract
Description
Technical Field
[0001] The present invention relates to ferrite powder and a method for producing the same. Background Art
[0002] Ferrite resin composite materials (resin compositions) composed of ferrite powder and resin are widely used in various applications represented by electromagnetic wave shielding materials. The composite material is made by mixing ferrite powder as a filler with a resin, and is formed into a shape such as a sheet to become a molded body (composite). At this time, if the shape of the particles constituting the ferrite powder is close to a sphere, the fluidity during molding increases, and the filling rate of the ferrite powder in the composite increases. Therefore, the moldability can be made good, and the characteristics such as electromagnetic wave shielding performance are also good. From this point of view, focusing on the ferrite powder composed of spherical particles, a scheme for making such spherical particles by a spraying method is proposed.
[0003] For example, Patent Document 1 (International Publication No. 2017 / 212997) discloses a ferrite particle, which is a single crystal ferrite particle with an average particle size of 1 to 2000 nm and a perfect spherical particle shape, characterized in that the ferrite particle contains substantially no Zn, contains 3 to 25 weight % Mn, and contains 43 to 65 weight % Fe, and the real part μ' of the complex magnetic permeability measured using a molded body composed of the ferrite particles and a binder resin has a maximum value in the frequency band of 100 MHz to 1 GHz. It is recorded that the ferrite particles are manufactured by spraying granules composed of a ferrite raw material in the atmosphere to ferriteize it, and then, after rapid cooling and solidification, only particles with a particle size within a specified range are recovered. When used as an electromagnetic wave protection material for electronic equipment, it is possible to stably shield wide-band electromagnetic waves that need to be shielded regardless of the frequency (claims 1,
[0039] and
[0078] of Patent Document 1).
[0004] Patent document 2 (International Publication No. 2017 / 169316) discloses a ferrite particle characterized by being a single crystal with an average particle size of 1 to 2000 nm, being a Mn-based ferrite particle with a true spherical particle shape, and having a saturation magnetization of 45 to 95 Am 2 / kg, it is recorded that a ferrite raw material containing Mn and Fe is sprayed in the atmosphere to ferrite it, and then it is quenched and solidified, and only particles with a particle size within a specified range are recovered to obtain a higher saturation magnetization and excellent dispersibility in resins, solvents or resin compositions (claims 1,
[0033] and
[0089] of patent document 2).
[0005] Patent document 3 (Patent Publication No. 2016-060682) discloses a spherical ferrite powder, characterized in that it contains ferrite particles with a particle size of less than 11 μm at a rate of 15 to 30% by weight, and the volume average particle size is 10 to 50 μm. The following contents are recorded: the conditioned granules are sprayed in the atmosphere to be ferriteized, and when used as a filler, the filling and moldability are good, and the workability is excellent, and the resistance is high. Therefore, the spherical ferrite powder is made into a resin composition together with a resin, and the molded body can be used in various applications represented by IC sealants for electromagnetic wave absorption (claims 1,
[0058] and
[0093] of patent document 3).
[0006] Patent document 4 (Japanese Patent Gazette No. 2005-015303) discloses a method for producing spherical powder, which is characterized in that it includes: a surface treatment step, in which a treatment agent composed of a raw material powder, a higher fatty acid, or its derivatives, a higher hydrocarbon, or at least one of a higher alcohol is heated to a specified temperature and then stirred, thereby surface treating the raw material powder; and a spherical powder generation step, in which the raw material powder after the surface treatment is put into a combustion flame generated in a combustion furnace and melted to spheroidize, and further the raw material powder is moved to the outside of the combustion flame and solidified to obtain a spherical powder (claim 1 of patent document 4).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2017 / 212997
[0010] Patent Document 2: International Publication No. 2017 / 169316
[0011] Patent Document 3: Japanese Patent Application Publication No. 2016-060682
[0012] Patent Document 4: Japanese Patent Application Publication No. 2005-015303 Summary of the invention
[0013] Technical problem to be solved by the invention
[0014] However, the inventors of the present invention have found that even when ferrite powder is produced by the spraying method, the ferrite powder sometimes contains many irregularly shaped particles in addition to the spherical particles. Such ferrite powder containing irregularly shaped particles has problems in that the magnetic properties, especially the saturation magnetization, are low, and the filler filling rate is not high when applied to a resin composition.
[0015] The inventors of the present invention have further studied and found that ferrite powder composed of true spherical particles containing carbon-hydrogen-oxygen (C-H-O) compounds and having a carbon content limited to a specific range can suppress the inclusion of irregular particles, and as a result, it is possible to suppress the reduction of saturation magnetization or the reduction of filler filling rate. In addition, it is also found that when the ferrite powder is used in a resin composition, the curing performance of the resin is excellent.
[0016] The present invention has been accomplished based on such findings, and an object of the present invention is to provide a ferrite powder and a method for producing the ferrite powder which prevents a decrease in saturation magnetization or a decrease in filler filling rate and has excellent resin curing performance.
[0017] Technical means for solving technical problems
[0018] The present invention includes the following aspects (1) to (5). It should be noted that in this specification, the expression "to" includes both numerical values. That is, "X to Y" is synonymous with "X or more and Y or less".
[0019] (1) A ferrite powder comprising true spherical ferrite particles,
[0020] The ferrite powder contains 54.0 to 70.0 mass % of iron (Fe) and 3.5 to 18.5 mass % of manganese (Mn), has an average volume particle size of 2.0 to 20.0 μm, and has a carbon content of 0.100 mass % or less.
[0021] (2) The ferrite powder according to (1) above, wherein the average shape factor SF-1 of the ferrite powder is 100 to 110.
[0022] (3) A method for producing the ferrite powder of (1) or (2) above, comprising the following steps:
[0023] The process of mixing ferrite raw materials to prepare a raw material mixture;
[0024] The step of pre-granulating the raw material mixture to prepare pre-granulated material;
[0025] The step of pre-sintering the pre-granulated material to produce a pre-sintered material;
[0026] The process of crushing the calcined product to produce calcined powder;
[0027] A step of adding and mixing a lubricant in an amount of 0.5 to 13.0 mass % to the calcined powder to prepare a spraying raw material; and
[0028] The step of thermally spraying the thermal spraying raw material to produce a thermal sprayed object.
[0029] (4) In the method of (3) above, the lubricant is of the general formula: CH3·(CH2) m A compound represented by COOH (wherein m is an integer of 10 to 16).
[0030] (5) In the method of (3) or (4) above, the thermal spraying raw material is a granulated material or an aggregate, and the volume average particle size of the granulated material or the aggregate is larger than the primary particle size of the calcined powder.
[0031] Effects of the Invention
[0032] According to the present invention, there are provided a ferrite powder and a method for producing the same, which prevents a decrease in saturation magnetization or a decrease in filler filling rate and is excellent in the curing property of a resin. DETAILED DESCRIPTION
[0033] A specific embodiment of the present invention (hereinafter referred to as "this embodiment") will be described. It should be noted that the present invention is not limited to the following embodiment, and various modifications can be made within the scope of the present invention.
[0034] Ferrite powder
[0035] The ferrite powder of this embodiment is composed of true spherical ferrite particles. That is, the ferrite powder includes a plurality of true spherical ferrite particles. In addition, the ferrite powder contains 54.0 to 70.0 mass% of iron (Fe) and 3.5 to 18.5 mass% of manganese (Mn), and the average volume particle size is 2.0 to 20.0 μm. In addition, the carbon content of the ferrite powder is 0.100 mass% or less.
[0036] By forming the ferrite powder from true spherical ferrite particles, when the ferrite powder is used as a filler in a resin composition (ferrite resin composite material), the formability and filling properties can be excellent. That is, the spherical particles smoothly avoid contact with other particles during forming. Therefore, the fluidity during forming is good and the filling is dense. In contrast, the formability and filling properties of particles with anisotropic shapes (indeterminate shapes) such as plate-like or needle-like particles are poor. In addition, in this specification, indeterminate shaped particles include anisotropic shaped particles, which are used in contrast to definite shaped particles such as spherical particles.
[0037] The ferrite powder of the present embodiment contains 54.0-70.0 mass % of iron (Fe) and 3.5-18.5 mass % of manganese (Mn). Although not limited, the remainder is mainly oxygen (O) and inevitable impurities. The ferrite powder has a component of manganese (Mn) ferrite. Here, manganese (Mn) ferrite does not contain zinc (Zn) in an amount exceeding the level of inevitable impurities. Therefore, it is distinguished from manganese (Mn)-zinc (Zn) ferrite to which zinc (Zn) is actively added. In addition, inevitable impurities are components that are inevitably mixed in during the manufacturing process, and refer to components whose content is less than 5000 ppm. As inevitable impurities, silicon (Si), aluminum (Al), calcium (Ca), chlorine (Cl), boron (B), zirconium (Zr) and chromium (Cr) can be cited.
[0038] When the iron content of manganese (Mn) ferrite is too little or too much, the imaginary part of the magnetic permeability (μ") and tanδ at 100 MHz will increase. Therefore, when the ferrite powder is applied to the resin composition, the saturation magnetic flux density may decrease or the magnetic loss may increase. Therefore, in the present embodiment, the iron (Fe) content is limited to 54.0 mass% or more, and the manganese (Mn) content is limited to 18.5 mass% or less. The iron content is preferably 58.0 mass% or more, and more preferably 60.0 mass% or more. In addition, the manganese content is preferably 10.0 mass% or less, and more preferably 9.0 mass% or less. On the other hand, In the case of excessive iron content or too little manganese content, the ferrite component may be close to easily oxidized magnetite, and oxidation causes the saturation magnetization to decrease. In addition, the real part of the magnetic permeability (μ') in 100MHz becomes smaller. Therefore, in this embodiment, the iron (Fe) content is limited to less than 70.0 mass%, and the manganese (Mn) content is limited to more than 3.5 mass%. The iron content is preferably less than 69.0 mass%, and more preferably less than 67.0 mass%. In addition, the manganese content is preferably more than 6.0 mass%, and more preferably more than 7.0 mass%. In addition, the total of iron and manganese will not exceed 73.5 mass%.
[0039] The average volume particle size (D50) of the ferrite powder of the present embodiment is 2.0 to 20.0 μm. If the volume average particle size is less than 2.0 μm, the viscosity of the monomer becomes too high when the ferrite powder is used as a filler in a resin composition. Therefore, it may not be possible to increase the filler filling rate. The volume average particle size is preferably greater than 2.5 μm, more preferably greater than 3.0 μm. On the other hand, when the volume average particle size is greater than 20.0 μm, the magnetic loss (tan δ) becomes excessively large, and the resin composition may not be used at high frequencies. The volume average particle size is preferably less than 15.0 μm, more preferably less than 10.0 μm, further preferably less than 7.0 μm, and particularly preferably less than 5.0 μm.
[0040] The ferrite powder of the present embodiment has a carbon content of 0.100% by mass or less. The carbon is a component caused by a carbon-hydrogen-oxygen compound. In addition, the carbon-hydrogen-oxygen compound is mainly a component of the lubricant added when the ferrite powder is manufactured. If the ferrite powder contains too much carbon-hydrogen-oxygen compound, when the ferrite powder is used as a filler in the resin composition, the viscosity of the resin composition before curing may increase, or the curing of the resin may be hindered. Although the detailed mechanism is unclear, it is believed that the carbon-hydrogen-oxygen compound derived from the lubricant is a compound with a main chain without a functional group, so although it does not react directly with the resin, the viscosity may increase due to the mixing of the above-mentioned carbon-hydrogen-oxygen compound in the resin molecule, or adverse effects may occur during curing. The carbon content is preferably 0.080% by mass or less, and more preferably 0.060% by mass or less. On the other hand, the lower limit of the carbon content is not particularly limited. However, if the lubricant is too little, irregular particles are easily mixed into the ferrite powder. The irregular shaped particles cause the magnetic properties and filling properties to deteriorate. Therefore, the carbon content is preferably 0.010 mass % or more, more preferably 0.015 mass % or more, and even more preferably 0.030 mass % or more. In addition, less than 0.010 weight % of carbon is a component derived from substances other than the lubricant attached to the ferrite particles.
[0041] The ferrite powder preferably contains ferrite particles containing a carbon-hydrogen-oxygen (C-H-O) compound. The compound mainly contains carbon (C), hydrogen (H) and oxygen (O), and may also be a component consisting only of carbon, hydrogen and oxygen. If a lubricant is not added during the manufacture of the ferrite powder, the supply of raw materials in the spraying process becomes unstable. Therefore, a large amount of raw materials pass through the spraying flame (flame) and spheroidization is not sufficiently performed, and irregular shaped particles are mixed into the ferrite powder. As a result, the magnetic properties of the ferrite powder and the filling properties of the resin composition are deteriorated. In addition, the firing based on the spraying is not sufficiently performed or the oxygen concentration of the spraying flame increases, resulting in a decrease in saturation magnetization. The carbon-hydrogen-oxygen compound is preferably of the formula: CH3·(CH2) n ·COOCH3 (where n is an integer from 6 to 9), among which methyl decanoate (CH3·(CH2)8·COOCH3) with n=8 is more preferred. It is believed that by using lauric acid as a lubricant, the ferrite powder obtained after spraying contains methyl decanoate.
[0042] The average shape factor SF-1 of the ferrite powder is preferably 100 to 110. SF-1 is an index of the sphericity of the particles (powder), and is 100 in a perfect sphere, and increases as it is further from the sphere. By setting SF-1 to 110 or less, the fluidity of the powder is improved, and the formability and filling properties are further improved. SF-1 is more preferably 108 or less, more preferably 105 or less, and particularly preferably 103 or less.
[0043] The average shape factor SF-1 of the ferrite powder is obtained by obtaining the shape factor SF-1 of each particle for a plurality of ferrite particles and calculating the average value. The SF-1 of the ferrite particles can be obtained by measuring the horizontal Feret diameter R (unit: μm), the projected circumference L (unit: μm) and the projected area S (unit: μm) of the particles. 2 ), and is obtained according to the following formula (1).
[0044] [Mathematical formula 1]
[0045]
[0046] The ferrite powder preferably has a content ratio of particles (irregular shaped particles) having an SF-1 greater than 103.6 of 15.0 number % or less, more preferably 10.0 number % or less, even more preferably 7.0 number % or less, particularly preferably 6.0 number % or less, and most preferably 5.0 number % or less. In this way, by reducing the content ratio of particles (irregular shaped particles) having a larger SF-1, when the ferrite powder is used as a filler in a resin composition (ferrite resin composite material), the formability and filling properties are more excellent. The lower limit of the content ratio of irregular shaped particles is not particularly limited, but is typically 1.0 number % or more, and more typically 3.0 number % or more.
[0047] Method for producing ferrite powder
[0048] The manufacturing method of the ferrite powder of the present embodiment includes the following steps: a step of mixing ferrite raw materials to prepare a raw material mixture (raw material mixing step); a step of pre-granulating the raw material mixture to prepare a pre-granulated product (pre-granulation step); a step of pre-sintering the pre-granulated product to prepare a pre-sintered product (pre-sintering step); a step of crushing the pre-sintered product to prepare a pre-sintered powder (crushing step); a step of adding and mixing 0.5 to 13.0 mass % of a lubricant to the pre-sintered powder to prepare a spraying raw material (pre-treatment step); and a step of spraying the spraying raw material to prepare a sprayed product (spraying step). The details of each step are described below.
[0049] <Raw material mixing process>
[0050] First, ferrite raw materials are mixed to make a raw material mixture. As the ferrite raw materials, known ferrite raw materials such as oxides, carbonates, hydroxides and / or chlorides can be used. For example, as iron raw materials and manganese raw materials, iron oxide (Fe2O3), manganese tetraoxide (Mn3O4), manganese dioxide (MnO2) and / or manganese carbonate (MnCO3) can be used. In addition, the mixing ratio of the raw materials is set to obtain a ferrite powder of the desired composition. The mixing of the raw materials can be carried out using a known mixer, and can be carried out by either or both of a dry method and a wet method.
[0051] <Pre-granulation process>
[0052] The obtained raw material mixture is pre-granulated to prepare a pre-granulated product. By providing a pre-granulation step, the input of raw materials in the pre-calcination step described later can be carried out stably and continuously. This is because the pre-granulated product is larger in size than the raw material and has excellent fluidity. In the pre-granulation step, a wet granulator such as a spray dryer can be used to granulate the slurried raw material mixture, or a dry granulation device such as a rotary compactor can be used to granulate the granular raw material mixture. Thus, a pre-granulated product with high sphericity and excellent fluidity can be obtained.
[0053] <Pre-firing process>
[0054] The obtained pre-granulated material is pre-calcined to produce a pre-calcined material. This promotes the ferritization of the raw material mixture. The pre-calcination temperature can be set to 600 to 1300° C. In addition, the oxygen concentration in the atmosphere can be adjusted between 0 and 21 volume % to promote ferritization. The pre-calcination can be carried out using a furnace such as a stationary electric furnace or a rotary drying furnace.
[0055] <Crushing process>
[0056] The obtained calcined product is crushed to prepare calcined powder. The crushing can be carried out using a known crusher, either dry or wet, or both. The crushing can be carried out using a medium mill such as a bead mill or a rod mill. In addition, a medium such as stainless steel, alumina, zirconia and / or steel balls can be used. In order to achieve the target crushed particle size, the size of the medium used in the coarse crushing and the fine crushing can be distinguished.
[0057] <Main granulation process>
[0058] If necessary, a process (main granulation process) for granulating the pre-calcined powder can also be provided. Thus, granules of the pre-calcined powder are obtained. In the main granulation process, the obtained pre-calcined powder is dispersed in water and slurried, and then the slurry is granulated with a spray dryer. The size of the granules is larger than the primary particle size of the pre-calcined powder, and the fluidity is excellent. Therefore, the supply stability of the raw material can be improved during the spraying process described later.
[0059] <Pre-treatment process>
[0060] Next, a lubricant is added and mixed in an amount of 0.5 to 13.0% by mass to the obtained calcined powder or its granules to prepare a spraying raw material. By adding a specified amount of lubricant, the fluidity of the spraying raw material is more excellent. Even if the lubricant is added in an excessive amount, there is no advantage in improving the fluidity. On the contrary, when ferrite powder is used as a filler in a resin composition, it is easy to cause problems such as hindering the curing of the resin. This is because the carbon content of the ferrite powder is too high. The amount of lubricant added is preferably 10.0% by mass or less, and more preferably 5.0% by mass or less. On the other hand, when no lubricant is added or the amount of lubricant added is too small, the fluidity of the spraying raw material deteriorates. Therefore, in the spraying process described later, the spraying raw material (calcined powder) is added to the device in a state that is unstable in time. As a result, when spraying in a state where the supply amount is too large, it is easy to produce particles that are not perfect spheres. Such particles that are not perfect spheres are indefinite in shape, and the ferritization reaction is not fully carried out inside. Therefore, the obtained ferrite powder contains many irregular-shaped particles, and its magnetic properties, especially saturation magnetization, are reduced. The amount of lubricant added is preferably 1.0 mass % or more, more preferably 1.5 mass %.
[0061] The calcined powder or its granulated product and the lubricant can be mixed using a known mixer, such as a Henschel mixer. In addition, the lubricant is preferably of the general formula: CH3·(CH2) m ·COOH (wherein m is an integer of 10 to 16), among which lauric acid (CH3·(CH2) 10 ·COOH) and / or stearic acid with m=16 (CH3·(CH2) 16 ·COOH). This is because such a compound is excellent in the effect of improving the fluidity of the spraying raw material, and is cheap and easy to obtain. In addition, when the main granulation step is set, the spraying raw material is a granulated material of pre-burned powder containing a lubricant, and when the main granulation step is not set, the spraying raw material is an aggregate of pre-burned powder containing a lubricant. The volume average particle size of the spraying raw material (granulated material and aggregate) is larger than the primary particle size of the pre-burned powder. Therefore, the fluidity of the spraying raw material is high in the subsequent spraying step.
[0062] <Spraying process>
[0063] Next, the spraying material is sprayed to produce a sprayed object. During the spraying, a mixed gas of a combustion gas and oxygen (total oxygen content) can be used as a combustible gas combustion flame source. The volume ratio of the combustion gas to oxygen (total oxygen content) is preferably 1:3.5 to 1:10.0, and more preferably 1:5 to 1:8.0. Thus, the formation of particles with high sphericity can be well promoted. As the combustion gas, combustible gases such as propane gas, propylene gas, and acetylene gas can be cited, among which propane gas can be preferably used. In addition, the supply amount of the spraying material is preferably 3.5 to 20 kg / hour, and more preferably 4.5 to 9 kg / hour. When the supply amount is too much, the spraying materials are easy to stick to each other, and it is difficult to make the ferritization reaction fully proceed to the inside of the particles. On the other hand, when the supply amount is too small, it becomes a cause of increased manufacturing costs.
[0064] The oxygen used for spraying can also be used for the purpose of conveying the raw material to the spraying flame. Therefore, it is divided into combustion oxygen used directly in the flame and raw material supply oxygen that is burned after conveying the raw material to the center of the spraying source. The carbon content in the ferrite powder after spraying can be controlled by the ratio of the capacity of oxygen and raw material supply oxygen. Expressed as total oxygen amount = combustion oxygen + raw material supply oxygen, the preferred capacity ratio of combustion oxygen: raw material supply oxygen = 95:5 to 80:20. If the ratio of combustion oxygen is greater than the above ratio (close to 100), the raw material supply capacity is reduced, and there is a possibility of clogging of the raw material supply pipe. If the ratio of combustion oxygen is less than the above ratio (less than 80), the raw material is widely supplied to the part that deviates from the center of the flame with the highest temperature, so that the carbon compound (lubricant) brought in with the raw material is prone to incomplete combustion, and the carbon content contained in the ferrite powder after spraying is sometimes increased. From the viewpoint of reducing the carbon content, combustion oxygen: raw material supply oxygen = 95:5 to 85:15 is more preferred, combustion oxygen: raw material supply oxygen = 95:5 to 87:13 is more preferred, and combustion oxygen: raw material supply oxygen = 95:5 to 89:11 is most preferred.
[0065] Furthermore, it is preferred that the combustion oxygen be set to a capacity required for complete combustion of the combustion gas × 0.85 times or more. For example, when propane gas is used as the combustion gas, it is preferred that the combustion oxygen have a capacity that is 4.25 times or more of that of the propane gas. By setting in this way, even if excess oxygen is supplied than the oxygen required for complete combustion of the combustion gas, the temperature drop of the spraying flame can be suppressed to a minimum, and incomplete combustion of the carbon compound (lubricant) brought in together with the raw material (pre-burned powder) can be prevented.
[0066] In addition, the combustion gas amount ratio is preferably not less than 1.05 and not more than 2.00. Here, the combustion gas amount ratio is the amount of combustion gas used for net combustion (Nm 3 The ratio of the raw material supply amount (kg / hour) to the raw material supply amount (kg / hour) can be calculated according to the following formula (2).
[0067] [Mathematical formula 2]
[0068]
[0069] The amount of combustion gas used for net combustion (Nm 3 / hour) can be calculated using the following formula (3) or the following formula (4).
[0070] [Mathematical formula 3]
[0071] Net combustion gas volume = oxygen volume supplied / 5···(3)
[0072] (The amount of combustion gas supplied × 5 - the amount of oxygen supplied ≥ 0)
[0073] [Formula 4]
[0074] Net combustion gas volume = supplied combustion gas volume (4)
[0075] (The amount of combustion gas supplied × 5 - the amount of oxygen supplied < 0)
[0076] As a transport gas for transporting the spraying raw material into the combustible gas, nitrogen, oxygen, air, etc. can be used. The flow rate of the transported spraying raw material is preferably 20 to 60 m / sec. The spraying is preferably carried out at a temperature of 1000 to 3500° C., more preferably 2000 to 3500° C. The particles ferritized by the spraying are quenched and solidified in an atmospheric atmosphere, and recovered by a cyclone separator or a filter to obtain a sprayed product.
[0077] <Classification process>
[0078] The obtained sprayed material can also be classified as needed. In the classification, the particle size can be adjusted to the desired particle size by using known methods such as wind classification (airflow classification), sieve classification, and sieve classification. In addition, the airflow classification by a cyclone separator can also be separated and recovered from particles with larger particle sizes in one process. In this way, a ferrite powder containing particles of an indeterminate shape can be obtained.
[0079] According to the present embodiment, a ferrite powder and a method for manufacturing the same are provided, which prevent the reduction of saturation magnetization or the reduction of filler filling rate, and have excellent curing performance of resin. The ferrite powder has a low content of irregular particles, which can prevent the problem of reduced saturation magnetization or reduced filler filling rate. In addition, the carbon content of the ferrite powder is limited to a specific range, which has the effect of excellent curing performance of resin.
[0080] As far as the inventors of the present invention know, such ferrite powders were not known in the past. Patent documents 1 to 3 disclose spherical ferrite particles produced by a spraying method, but the carbon content is not disclosed. In addition, Patent document 4 discloses a method for treating a raw material powder with a surface treatment agent such as a higher fatty acid, but does not mention the carbon content of the obtained powder, and does not recognize the curing performance of the resin. In addition, it can be considered that in the method of Patent document 4, the raw material powder is not granulated, and in the case of such a powder, the fluidity during manufacturing is poor.
[0081] Ferrite resin composite material
[0082] The ferrite powder of this embodiment can be applied to a ferrite resin composite material (resin composition). The ferrite resin composite material includes ferrite powder and resin. By using the ferrite powder of this embodiment, a composite material having a high filler filling rate, excellent magnetic properties (saturation magnetic flux density, magnetic loss, etc.), and further excellent resin curing performance can be obtained.
[0083] As the resin constituting the composite material, for example, epoxy resin, polyurethane resin, acrylic resin, silicone resin, polyamide resin, polyimide resin, polyamide imide resin, fluororesin or a combination thereof can be cited. Here, the silicone resin can also be a modified silicone resin modified with acrylic acid, urethane, epoxy and / or fluorine.
[0084] The ratio of ferrite powder to the total solid content in the composite material is preferably 50 to 95% by mass, more preferably 80 to 95% by mass. In addition, the ratio of resin to the total solid content in the composite material is preferably 5 to 50% by mass, more preferably 5 to 20% by mass. By setting the ratio of ferrite powder to resin within the above range, the dispersion stability of ferrite powder in the composite material, the storage stability and formability of the composite material are excellent, and the mechanical strength, electromagnetic wave shielding performance and other properties of the composite (molded body) obtained by molding the composite material are more excellent.
[0085] The composite material may contain other components besides the ferrite powder and the resin. Examples of such components include solvents, fillers (organic fillers, inorganic fillers), plasticizers, antioxidants, dispersants, colorants such as pigments, and thermally conductive particles.
[0086] Such ferrite resin composite material can be applied to electromagnetic wave shielding materials, electronic materials or electronic components. Electromagnetic wave shielding materials, electronic materials or electronic components can be made by forming composite materials using known methods. The forming method is not particularly limited, and for example, compression molding, extrusion molding, injection molding, blow molding or wheel rolling molding can be cited. In addition, it can also be a method in which a coating film of the composite material is formed on a substrate.
[0087] [Example]
[0088] The present invention will be further specifically described by the following examples. However, the present invention is not limited to the following examples.
[0089] (1) Preparation of ferrite powder
[0090] [Example 1]
[0091] <Raw material mixing process and pre-granulation process>
[0092] Iron oxide (Fe2O3) and manganese tetraoxide (Mn3O4) were used as raw materials, and the raw materials were weighed and mixed in such a way that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn=8:1. Water was added to the obtained mixture, and the mixture was crushed using a wet bead mill to prepare a slurry with a solid content of 50% by mass. Then, the slurry was granulated using a spray dryer to prepare a pre-granulated product.
[0093] <Preliminary calcination and pulverization process>
[0094] The obtained pre-granulated material was pre-calcined to produce a pre-calcined material. The pre-calcination was performed using a rotary drying furnace at a pre-calcination temperature of 780°C and an atmospheric atmosphere. Next, the obtained pre-calcined material was pulverized using a dry bead mill to produce a pre-calcined powder. The particle size (primary particle size) of the obtained pre-calcined powder was 4.2 μm.
[0095] <Main granulation process>
[0096] Water was added to the obtained calcined powder, and the powder was crushed using a wet bead mill to prepare a slurry with a solid content of 50% by mass. The particle size (primary particle size) of the crushed powder in the slurry was 4.2 μm. Next, the slurry was granulated using a spray dryer. The average particle size of the obtained granules (calcined powder granules) was 50 μm.
[0097] <Pre-treatment process>
[0098] Lauric acid was added as a lubricant to the obtained granules, and the mixture was mixed using a Henschel mixer. At this time, the amount of the lubricant (lauric acid) added was 15.0 parts by mass (15.0% by mass) relative to 100.0 parts by mass of the granules. Thus, a thermal spraying raw material was obtained.
[0099] <Spraying process>
[0100] The granulated material (spraying raw material) to which the lubricant is added is sprayed and quenched in a combustible gas combustion flame. During spraying, the ratio of the propane gas flow rate to the total oxygen flow rate is set to 1:5.42, and the raw material supply rate is set to 1.13 according to the combustion gas ratio. Next, the cooled particles are recovered by a cyclone separator set on the downstream side of the airflow to obtain a sprayed material. At this time, the combustion oxygen: raw material supply oxygen = 89.5:10.5.
[0101] <Grading process>
[0102] Coarse powder was removed from the obtained sprayed product using a sieve, and fine powder was further removed by air flow classification to obtain ferrite powder consisting of ferrite particles. Table 1 also shows the production conditions of the ferrite powder.
[0103] [Example 2]
[0104] In the pretreatment step, ferrite powder was produced in the same manner as in Example 1 except that the amount of the lubricant (lauric acid) added was 5.0 parts by mass (5.0% by mass) based on 100.0 parts by mass of the granulated product.
[0105] [Example 3]
[0106] In the pretreatment step, ferrite powder was produced in the same manner as in Example 1 except that the amount of the lubricant (lauric acid) added was 3.0 parts by mass (3.0% by mass) based on 100.0 parts by mass of the granulated product.
[0107] [Example 4]
[0108] In the pretreatment step, ferrite powder was produced in the same manner as in Example 1 except that the amount of the lubricant (lauric acid) added was 1.5 parts by mass (1.5% by mass) based on 100.0 parts by mass of the granulated product.
[0109] [Example 5]
[0110] Ferrite powder was prepared in the same manner as in Example 1 except that the lubricant (lauric acid) was not added to the granulated product.
[0111] [Example 6]
[0112] In the mixing and pulverizing step, the ferrite powder was produced in the same manner as in Example 4 except that iron (Fe) and manganese (Mn) were weighed and mixed so that the molar ratio was Fe:Mn=3:1. In the main granulation step, the particle size (primary particle size) of the pulverized powder in the slurry was 4.7 μm.
[0113] [Example 7]
[0114] In the mixing and pulverizing step, iron (Fe) and manganese (Mn) were weighed and mixed so that the molar ratio was Fe:Mn=14:1, and the ferrite powder was produced in the same manner as in Example 4. In the main granulation step, the particle size (primary particle size) of the pulverized powder in the slurry was 3.9 μm.
[0115] [Example 8]
[0116] Except for changing the classification conditions in the classification step, the ferrite powder was produced in the same manner as in Example 4. In the main granulation step, the particle size (primary particle size) of the pulverized powder in the slurry was 4.2 μm.
[0117] [Example 9]
[0118] Except for changing the classification conditions in the classification step, the ferrite powder was produced in the same manner as in Example 4. In the main granulation step, the particle size (primary particle size) of the pulverized powder in the slurry was 4.2 μm.
[0119] (2) Evaluation of ferrite powder
[0120] The ferrite powders of Examples 1 to 9 were evaluated as follows.
[0121] <Chemical Analysis (ICP)>
[0122] The metal content of the ferrite powder was determined as follows. First, 0.2 g of the sample (ferrite powder) was weighed, and 60 ml of pure water, 20 ml of 1N hydrochloric acid, and 20 ml of 1N nitric acid were added thereto and heated to prepare an aqueous solution in which the sample was completely dissolved. The obtained aqueous solution was placed in an ICP analyzer (Shimadzu Corporation, ICPS-10001V) to determine the metal content.
[0123] <Carbon content>
[0124] The carbon content of the ferrite powder was measured by infrared absorption method. Specifically, 1 g of the ferrite powder was burned in an oxygen gas flow to convert the carbon contained in the ferrite powder into carbon dioxide. An infrared absorption detector (LECO JAPAN Contract Co., Ltd., carbon-sulfur analyzer CS200) was used to measure the infrared absorption of carbon dioxide and calculate the carbon content.
[0125] <Analysis of carbon-containing compounds (GC-MS)>
[0126] The carbon-containing compounds attached to the ferrite powder were analyzed using a high-resolution mass analyzer GC / MS. 5 g of ferrite powder was weighed and placed in a beaker with an internal volume of 200 ml. 500 ml of methyl ethyl ketone (MEK) was further added and ultrasonic treatment was performed for 5 minutes to extract the organic components attached to the ferrite powder. The extracted MEK solution was filtered and the obtained filtrate was used as the test solution. The analysis conditions of the high-resolution mass analyzer GC / MS are shown below.
[0127] - Gas chromatography: Agilent Technologies, 6890N
[0128] -Mass Analyzer: Agilent Technologies, 5973N
[0129] -Column: Agilent Technologies, DB.5MS (film thickness 0.25μm)
[0130] -Heating inlet device: Parkin Elmer, Turbo Matrix 650ATD
[0131] - Temperature conditions: 50°C (2 minutes) → 280°C (18 minutes)
[0132] - Heating speed: 20℃ / min
[0133] -Carrier gas flow rate: Helium 1ml / min
[0134] -Injection method: No split 0.5
[0135] -Injection port temperature: 280℃
[0136] -Interface: 280℃
[0137] -Measurement mass range: m / z 29~600
[0138] -Injection volume: 1μl
[0139] In addition, the identification of carbon-containing compounds was performed as follows. Using an analytical device (Agilent Technologies, 5973N), the detection peaks derived from the device and from MEK were excluded from the TIC chromatogram, and the remaining detection peaks were searched in the library. The compound with the highest library consistency rate in the mass spectrum model was identified as the incidental carbon-containing compound in the ferrite powder.
[0140] <Particle size distribution>
[0141] Determine the particle size distribution of ferrite powder. First, put 10g of the sample and 80ml of water into a 100ml beaker, and add two drops of sodium hexametaphosphate as a dispersant. Next, use an ultrasonic homogenizer (SMT Co., Ltd., UH-150 model) to disperse. At this time, set the output level of the ultrasonic homogenizer to 4, and disperse for 20 seconds. Thereafter, remove the bubbles formed on the surface of the beaker, and introduce it into a laser diffraction particle size distribution measuring device (Shimadzu Corporation, SALD-7500nano) for measurement. Through this measurement, the 10% diameter (D10), 50% diameter (volume average particle size, D50) and 90% diameter (D90) in the volume particle size distribution are obtained. Here, the measurement conditions are set to a pump speed of 7, a built-in ultrasonic irradiation time of 30, and a refractive index of 1.70-050i.
[0142] <BET specific surface area>
[0143] The BET specific surface area of ferrite powder is measured using a specific surface area measuring device (Mountech Co., Ltd., Macsorb HM model-1208). First, about 10 g of the obtained ferrite powder is placed on a medicine paper, and the gas is removed with a vacuum dryer to confirm that the vacuum degree is below -0.1 MPa. Thereafter, the moisture attached to the surface of the particles is removed by heating at 200°C for 2 hours. About 0.5 to 4 g of the ferrite powder after the moisture is removed is placed in a standard sample chamber dedicated to the measuring device and accurately weighed with a precision balance. Next, the weighed ferrite particles are set at the measuring port of the measuring device for measurement. The measurement is performed by the 1-point method. The measurement atmosphere is set to a temperature of 10 to 30°C and a relative humidity of 20 to 80% (no condensation).
[0144] <Tap density>
[0145] The tap density of the ferrite powder was measured using a USP tap density measuring device (Hosokawa Micron Co., Ltd., Powder Tester PT-X) in accordance with JIS Z 2512-2012.
[0146] <Shape factor (SF-1)>
[0147] The average shape factor (SF-1) of the ferrite powder was obtained as follows. The ferrite powder was analyzed using a particle image analyzer (Malvern Panalytical, Morphologi G3). During the analysis, an image analysis was performed on each of the 30,000 particles in the powder, and the maximum length (horizontal Feret diameter) R (unit: μm), the projected circumference L (unit: μm), and the projected area S (unit: μm) were automatically measured. 2) Next, the SF-1 of each particle was calculated according to the following formula (1), and the average value thereof was taken as the SF-1 of the ferrite powder.
[0148] [Mathematical formula 5]
[0149]
[0150] Furthermore, the number of particles having SF-1 greater than 103.6 (irregular-shaped particles) was counted, and the irregular-shaped particle ratio was determined according to the following formula (5).
[0151] [Mathematical formula 6]
[0152]
[0153] <Magnetic properties (saturation magnetization, residual magnetization, and coercive force)>
[0154] The magnetic properties (saturation magnetization, residual magnetization and coercive force) of ferrite powder were measured as follows. First, the sample was placed in a chamber with an inner diameter of 5 mm and a height of 2 mm, and set in a vibrating sample type magnetic measuring device (Toei Industry Co., Ltd., VSM-C7-10A). The magnetic field was applied and scanned to 5 kOe, and then the applied magnetic field was reduced to draw a hysteresis curve. Based on the data of the obtained curve, the saturation magnetization σs, residual magnetization σr and coercive force Hc of the sample were obtained.
[0155] <Magnetic Permeability>
[0156] The magnetic permeability of ferrite powder was measured using an RF impedance / material analyzer (Agilent Technology Co., Ltd., E4991A) and a magnetic material measuring electrode (16454A). First, 9 g of ferrite powder and 1 g of binder resin (Kynar301F: polyvinylidene chloride) were placed in a polyethylene container (content 100 ml), and stirred and mixed using a ball mill at a rotation speed of 100 rpm. About 0.6 g of the obtained mixture was filled into a mold (inner diameter 4.5 mm, outer diameter 13 mm), and a press was used to pressurize at a pressure of 40 MPa for 1 minute to produce a molded body. The obtained molded body was heated and cured at 140°C for 2 hours using a hot air dryer to prepare a measurement sample. The obtained measurement sample was set in the RF impedance / material analyzer, and the outer diameter, inner diameter and height of the measurement sample measured in advance were input. The amplitude was set to 100 mV during the measurement, and the frequency range of 1 MHz to 3 GHz was scanned using a logarithmic scale. The real part μ' and imaginary part μ" of the complex permeability at a frequency of 100 MHz were obtained, and the loss coefficient tanδ was calculated according to the following formula (6).
[0157] [Mathematical formula 7]
[0158]
[0159] <Resin curing performance>
[0160] Ferrite powder is applied to resin composition to evaluate the resin curing performance. First, 80 parts by mass of ferrite powder, 18 parts by mass of epoxy resin and 2 parts by weight of curing agent are dispersed and mixed using a rotation-revolution type mixer to prepare a resin composition. The obtained resin composition is dried at 120°C for 5 minutes. The dried resin composition is heated at 180°C to promote curing, and the curing time when the resin curing degree reaches more than 95% is obtained. According to the obtained curing time, the evaluation is performed as follows.
[0161] A: Curing time is greater than Std×1.00 and less than Std×2.00
[0162] B: Curing time is greater than Std×2.00 and less than Std×3.00
[0163] C: Curing time is Std×3.00 or more
[0164] Here, the so-called resin curing degree refers to the degree of progress of the curing reaction of the resin (reaction rate). The resin curing degree of the unreacted material is 0%, and the resin curing degree of the reacted material is 100%. The resin curing degree is obtained using an FT-IR (Fourier transform infrared spectrometer) device. Specifically, the resin is irradiated with infrared light to make it pass through or split it to obtain an FT-IR spectrum, and the progress of the curing reaction of the resin is analyzed using this spectrum. In addition, the spectra of the unreacted material, the 100% reacted material, and the resin to be measured are compared, and the resin curing degree is obtained by comparing the peak intensity of each sample in the area where the difference is most observed. In addition, the curing time of Example 4 is used as the benchmark (Std) to calculate the curing time of each sample.
[0165] In addition, the drying conditions of the resin composition are not limited to the above conditions. It is preferred to dry the resin composition in a manner that the content of the organic solvent is 10% by mass or less, more preferably 5% by mass or less. The drying conditions can be appropriately set by simple experiments. It also varies depending on the amount of organic solvent in the varnish (resin composition). For example, a varnish containing 30 to 60% by mass of an organic solvent can be dried at 50 to 150°C for about 3 to 10 minutes. In addition, the determination of the degree of resin curing is not limited to the use of FT-IR, and a dispersed infrared spectrophotometer or the like can also be used.
[0166] (3) Results
[0167] The evaluation results obtained in Examples 1 to 9 are shown in Tables 1 and 2. As shown in Tables 1 and 2, in Examples 1 to 9, ferrite powders having a manganese ferrite component and a volume average particle size (D50) of 2.6 to 7.5 μm were obtained. The ferrite powders contained true spherical particles.
[0168] The samples of Examples 2 to 4 and 6 to 9, in which the lubricant (lauric acid) is added in an amount of 1.5 to 5.0% by mass, contain methyl decanoate, a carbon-hydrogen-oxygen compound, and the carbon content is 0.012 to 0.080% by mass. These samples have a small proportion of irregular particles (the proportion of particles with SF-1 greater than 103.6) of less than 6.2% by number, and there are no problems in terms of magnetic properties and magnetic permeability. In addition, there are no problems in terms of resin curing performance when applied to resin compositions. In particular, the samples of Examples 3, 4, 6, 7 and 9, in which the carbon content is 0.012 to 0.060% by mass, have better resin curing performance. In addition, the sample of Example 5, in which no lubricant is added, also has excellent resin curing performance. In addition, although no lubricant is added to the sample of Example 5 during its manufacture, it contains a trace amount (0.002% by mass) of carbon. It is speculated that the carbon may come from the soot during spraying, but the details are not clear.
[0169] In contrast, the sample of Example 1, in which the lubricant addition amount was 15.0 mass %, had a high carbon content (0.200 mass %) and had a long resin curing time when used in a resin composition, which caused problems in the resin curing performance.
[0170] [Table 1]
[0171]
[0172] [Table 2]
[0173]
Claims
1. A ferrite powder, comprising true spherical ferrite particles, wherein: The ferrite powder contains 54.0-70.0 mass % of iron (Fe) and 3.5-18.5 mass % of manganese (Mn), has an average volume particle size of 2.0-20.0 μm, and has a carbon content of 0.010 mass % or more and 0.100 mass % or less. The ferrite particles contain carbon-hydrogen-oxygen (C—H—O) compounds, The content ratio of particles having SF-1 greater than 103.6, i.e., irregular-shaped particles, in the ferrite powder is 10.0% by number or less.
2. The ferrite powder according to claim 1, wherein The average shape factor SF-1 of the ferrite powder is 100-110.
3. A method for producing the ferrite powder according to claim 1 or 2, comprising the following steps: The process of mixing ferrite raw materials to prepare a raw material mixture; The step of pre-granulating the raw material mixture to prepare pre-granulated material; The step of pre-sintering the pre-granulated material to produce a pre-sintered material; The process of crushing the calcined product to produce calcined powder; A step of adding and mixing 0.5 to 13.0 mass % of a lubricant to the calcined powder to prepare a spraying raw material; and The process of spraying the spraying raw material to produce the sprayed material; The lubricant is of the general formula: CH3·(CH2) m Compounds represented by COOH, in, m is an integer of 10 or more and 16 or less.
4. The method according to claim 3, wherein: The spraying raw material is a granulated material or an aggregate, and the volume average particle size of the granulated material or the aggregate is larger than the primary particle size of the calcined powder.
Citation Information
Patent Citations
Method of manufacturing spherical powder, spherical oxide powder and oxide powder
JP2005015303A
Spherical ferrite powder, resin composition containing spherical ferrite powder and molded body using resin composition
JP2016060682A
Ferrite particles, resin composition, and resin film
WO2017169316A1
Ferrite particles, resin composition and electromagnetic shielding material
WO2017212997A1
Mn ferrite powder, resin composition, electromagnetic wave shielding material, electronic material, and electronic component
WO2019159797A1